Engagement in HIV continuum of care: Another step needed to close the gap toward UNAIDS 90‐90‐90 targets among younger men in Rwanda. Issue 3 (1st March 2023) - Rwibasira, Gallican N.; Dzinamarira, Tafadzwa; Remera, Eric; Malamba, Samuel S.; Fazito, Erika; Mathu, Rachel; Matreja, Priyal; Cai, Haotian; Kayirangwa, Eugenie; Nsanzimana, Sabin
Abstract: In this study, we measured Rwandan men's engagement in HIV services based on the UNAIDS 90‐90‐90 targets and assessed factors associated with linkage to HIV services. We analyzed the Rwanda Population‐based HIV Impact Assessment (RPHIA) data for 15‐ to 64‐year‐old males. We conducted bivariate analysis to assess the distribution and association of sociodemographic characteristics with UNAIDS 90‐90‐90 targets. We adjusted multivariable models to understand the effect measurement of associated factors and determine the factors that best predict the achievement of UNAIDS 90‐90‐90. Of 13 780 males aged 15–64 years who participated in the RPHIA and consented to the blood draw and HIV testing, 302 had a positive HIV result, while 301 had valid responses to all variables analyzed in this paper and were included in the analysis. We found that age group was an explanatory and predictive factor for achievement of UNAIDS 90‐90‐90. Younger men living with HIV (MLHIV) are less likely to have achieved UNAIDS 90‐90‐90 compared to MLHIV 50–64 years old: adjusted odds ratio (aOR) for MLHIV aged 15–34 years was 0.21 (0.08–0.53) and aOR for MLHIV aged 35–49 years was 0.77 (0.36–1.66). To close the UNAIDS 90‐90‐90 gap in Rwanda, innovative service delivery strategies are needed to support young MLHIV to reach 90‐90‐90.